Characteristics of hybrid alkaline cement composites with high cement content: flash set and high compressive strength - Sungwoo Park; Kebede Alemayehu Moges; Siyu Wu; Sukhoon Pyo (Journal of Materials Research and Technology, 2022)
This paper explores hybrid alkaline cement composites with high cement content over 50%. Calcium (Ca) accelerates the strength development and improves the compressive strength of geopolymer. However, the mixing proportion of Ca in geopolymer has been limited because Ca significantly decreases the flow of fresh geopolymer. This study resolves the flow decline issue by mixing a part of the initial mixing water with cement before adding it into a metakaolin-based geopolymer, which is named hybrid alkaline cement composites (HACC) in this study. The cement/(metakaolin + cement) ratio investigated is up to 85%. Based on the initial setting time and compressive strength results, some unique characteristics of the HACC are observed: i) the material is set within 10 min and the 28-day compressive strength is over 80 MPa with 1:1 mixing ratio of geopolymer and cement paste, and ii) the compressive strength of HACC is not always higher with a lower w/c ratio of cement paste.